Correlation Between Global Stock Market And Cryptocurrency With Jci In Indonesia: A Time-Series Analysis Approach - Agiel, Agiel Muhammad Azri; Dias Satria (Contemporary Studies in Economic, Finance and Banking, 2025)
The ease of global investment by the WTO and the rise of world investment trends have begun to attract investors with the recovery period from the economic downfall due to Covid-19 and the Work From Home (WFH) trend which has made investment activities both in domestic, global and cryptocurrency stock markets increasingly in demand in recent years. This study aims to determine the relationship between the domestic stock market (JCI) or Indonesia from the global stock market (DJAI & Nikkei 225) and cryptocurrencies (Bitcoin and USDT) during 2018 to 2022, whether these variables have a correlation with each other. This research uses the Error Correction Model (ECM) method to process data. The findings obtained that DJAI and USDT have a correlation with JCI while Nikkei 225 has a significant correlation in the long term with JCI, but Bitcoin has no correlation with the JCI work path